Risk factors for road traffic accidents among drivers of public institutions in Ibadan, Nigeria (2007)
Recent studies have shown an increase in the rate of road traffic accident (RTA). Identifying the risk factors for this problem may provide a clue to possible effective intervention. This study aimed to determine the prevalence and risk factors for self reported RTA among drivers of educational institutions and make suggestions to promote safer driving. A cross sectional population study of motor vehicle drivers from the College of Medicine, University of Ibadan and University College Hospital (UCH) Ibadan was undertaken between December 2003 and January 2004. The study comprised of 99 motor vehicle drivers. 67 (67.7%) were from the College of Medicine, and 32 (32,3%) from the UCH. Response rate was 97,1 %. All were males, aged 38 to 60 years, mean 50.1 ± (SD= 4.8 years). The prevalence of self reported RTA was 16.2%. The cause of road traffic accidents included, mechanical fault (50%), bad road (12.5%). RTA prevalence was higher among older drivers (OR=1.7, 95%CI=0.5-5.9; P>0.05), drivers who had part time jobs (Odds ratio 2.6, 95% CI 1.1-6.3; X2 =4.5, P=O.03), and drivers with visual impairment (OR=1.6, 95% CI=0.9, X2 0.49, P > 0.05). The prevalence of RTA was lower amongst drivers who did not take alcohol, cola nut and other CNS stimulants while driving (OR 0.9, 95% CI=0.3-2.3, P >0.05). Regular maintenance of official vehicles and examination of drivers' eyes are recommended. Drivers should be discouraged from drugs and part jobs so as to ensure that they have enough time to rest and therefore prevent fatigue related RTA.